A Task Analysis of Client Re‐engagement: Therapeutic De‐escalation of High‐Conflict Coparents. - Anderson, Shayne R.; Sumner, Brock W.; Parady, Andrea; Whiting, Jason; Tambling, Rachel (Family Process, 2020)
Parents who are engaged in protracted conflict following a divorce are often referred to coparenting therapy. Episodes of intense conflict are common during these therapy sessions and often result in coparents disengaging from the therapist while they engage in escalating conflict with each other, potentially disrupting their progress in therapy. The purpose of this study was to identify how therapists successfully re‐engage clients in the session. To understand this process, 24 disengagement events (12 successful and 12 unsuccessful) from 13 cases were analyzed using a task analytic approach. The sample included coparent dyads referred by the judicial system to a high‐conflict coparenting therapy program. Task analysis was used to create a model of how re‐engagement unfolds in treatment. The empirical model that resulted has five phases: (1) disengagement from the therapeutic process, (2) disruption of the conflict, (3) de‐escalating the most escalated coparent, (4) de‐escalating the other coparent, and (5) therapist buffered re‐engagement. Successful episodes of re‐engagement tended to have therapists who remained active throughout the conflict episode, used structuring interventions aimed at disrupting and then regulating the most escalated partner, blocked attempts to re‐engage in conflict, and then repeated this process with the less escalated partner. Additional interventions that promote therapeutic re‐engagement are described for each phase, and implications for clinicians and researchers are discussed.